A Pilot Study of Low-Dose Zidovudine in Human Immunodeficiency Virus Infection - Collier, Ann C; Bozzette, Samuel; Coombs, Robert W; Causey, Dennis M; Schoenfeld, David A; Spector, Stephen A; Pettinelli, Carla B; Davies, Glenn; Richman, Douglas D; Leedom, John M; Kidd, Pamela; Corey, Lawrence (The New England journal of medicine, 1990)
ZIDOVUDINE prolongs survival in persons with advanced human immunodeficiency virus (HIV) disease and delays the progression of HIV infection. 1 2 3 The initially recommended doses of 1200 to 1500 mg a day are associated with hematologic toxicity that often requires the interruption of therapy. 2 , 4 5 6 With prolonged use, opportunistic infections and death eventually occur, 7 and regimens are therefore needed that enhance the efficacy and reduce the toxicity of zidovudine. Combination therapy with lower doses of antiviral drugs is one possible approach. Acyclovir, a nucleoside analogue with little or no intrinsic activity against HIV, has been reported to potentiate zidovudine's anti-HIV effect in vitro. . . .